2020
DOI: 10.1038/s41375-020-01018-y
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate use of JAK1/2 inhibitor ruxolitinib for severe COVID-19: a prospective observational study

Abstract: Overwhelming inflammatory reactions contribute to respiratory distress in patients with COVID-19. Ruxolitinib is a JAK1/ JAK2 inhibitor with potent anti-inflammatory properties. We report on a prospective, observational study in 34 patients with COVID-19 who received ruxolitinib on a compassionate-use protocol. Patients had severe pulmonary disease defined by pulmonary infiltrates on imaging and an oxygen saturation ≤ 93% in air and/or PaO2/FiO2 ratio ≤ 300 mmHg. Median age was 80.5 years, and 85.3% had ≥ 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 63 publications
4
66
0
Order By: Relevance
“…Of note, MF was the most represented among the MPNs (34%) and HU was the most common treatment (45.1%). Ruxo was used in 25% of cases, a figure that is consistent with recent reports on real-world clinical treatment of MPNs [8,9] and in agreement with the high prevalence of MF in our cohort. All the 135 hospitalized patients and 20 (50%) of those treated at home had COVID-19 diagnosis confirmed by a positive result on polymerase chain reaction testing of a nasopharyngeal sample; the remaining 20 patients managed at home were diagnosed based on highly suggestive symptomatology.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, MF was the most represented among the MPNs (34%) and HU was the most common treatment (45.1%). Ruxo was used in 25% of cases, a figure that is consistent with recent reports on real-world clinical treatment of MPNs [8,9] and in agreement with the high prevalence of MF in our cohort. All the 135 hospitalized patients and 20 (50%) of those treated at home had COVID-19 diagnosis confirmed by a positive result on polymerase chain reaction testing of a nasopharyngeal sample; the remaining 20 patients managed at home were diagnosed based on highly suggestive symptomatology.…”
Section: Discussionsupporting
confidence: 92%
“…Other three single arm not randomized studies were published so far about the use of Ruxolitinib in Covid-19 . All confirm a fast effect of the drug reducing markers on infection and improving signs of respiratory distress [21][22][23] The important role of lung hyperinflammation in Covid-19 19 is again supported by the present study.…”
Section: Accepted Articlesupporting
confidence: 85%
“…On the bases of all biological premises (62,115,(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129), and of our preliminary results, we firmly believe that ruxolitinib presents a strong potential in overcoming lung and systemic complications caused by JAK/STAT-mediated immune hyperactivation during COVID-19 disease. Indeed, while recent works in this field (123)(124)(125)127) demonstrated a promising activity of ruxolitinib in avoiding respiratory worsening and progression to mechanical ventilation in hyperinflamed patients at imminent risk to be admitted to ICU (by using different treatment schedules, including a dose escalation in case of not-responding patients), here we presented a case-report documenting the potential activity of the drug (with a slightly different 20-days schedule which include a preplanned dose intensification followed by a decalage phase) in patients already under mechanical ventilation, thus extending the possibility of using this drug in critical patients (our patient was indeed quickly intubated after treatment beginning and received ruxolitinib through a nasogastric tube). Anyway, while using different timings and schedules, all the studies reported a clinical benefit within few days from treatment starts without major signs of ruxolitinib-associated toxicities (mainly due to the short treatment courses) underscoring the need of larger studies (phase 3 studies are ongoing) to confirm the activity of the drug in hyperinflamed COVID-19 patients regardless of the respiratory support they need.…”
Section: Discussionmentioning
confidence: 60%